Job stress among staff nurses at Sarawak general Hospital in Kuching division Sarawak - Mohamed Pauzan, Bin Nuruddin. (2000)
This study focuses on perceived level job stress and coping strategies used by the staff nurse at the Sarawak General Hospital, Kuching. It was conducted through survey questionnaire at selected 15 units / wards of attachment.